TARGETING MUC1-C INHIBITS TWIST1 SIGNALING IN TRIPLE-NEGATIVE BREAST CANCER - Hata, Tsuyoshi (Mol Cancer Ther, 2019)
The oncogenic MUC1-C protein and the TWIST1 epithelial-mesenchymal transition transcription factor (EMT-TF) are aberrantly expressed in triple-negative breast cancer (TNBC) cells. However, there is no known association between MUC1-C and TWIST1 in TNBC or other cancer cells. Here we show that MUC1-C activates STAT3 and that MUC1-C and pSTAT3 drive induction of the TWIST1 gene. In turn, MUC1-C binds directly to TWIST1 and MUC1-C/TWIST1 complexes activate MUC1-C expression in an autoinductive circuit. The functional significance of the MUC1-C/TWIST1 circuit is supported by the demonstration that this pathway is sufficient for driving (i) the EMT-TFs, ZEB1 and SNAIL, (ii) multiple genes in the EMT program as determined by RNA-seq, and (iii) the capacity for cell invasion. We also demonstrate that the MUC1-C/TWIST1 circuit drives (i) expression of the stem cell markers SOX2, BMI1, ALDH1 and CD44, (ii) self-renewal capacity and (iii) tumorigenicity. In concert with these results, we show that MUC1-C and TWIST1 also drive EMT and stemness in association with acquired paclitaxel (PTX) resistance. Of potential therapeutic importance, targeting MUC1-C and thereby TWIST1 reverses the PTX refractory phenotype as evidenced by synergistic activity with PTX against drug-resistant cells. These findings uncover a master role for MUC1-C in driving the induction of TWIST1, EMT, stemness and drug resistance, and support MUC1-C as a highly attractive target for inhibiting TNBC plasticity and progression.